Transport Systems and Delivery of Cargo on East-West Routes (Studies in Systems, Decision and Control,, 2018)
This book discusses the problems of delivering goods from East and South-East Asia to Europe, presenting the regional transport problems experienced in Italy, Slovakia, Russia, Georgia, Kazakhstan, Uzbekistan and Poland. The book is divided into two parts. The first part is devoted to the analysis of various issues in global logistics and regional transport, which operate in transport corridors. The second part of the book focuses on solutions to some of the technical and informatics problems related to the organization of transportation along the East-West routes. Intended primarily for professionals involved in various aspects of cargo delivery along the East-West routes, the book is also useful for manufacturers, technical staff at logistics companies, managers, students of transport-related subjects, as well as for a wide range of readers interested in the current state of transport in different countries.